Research and development as an initiator of fixed kapital investment - Andrin Spescha; Martin Wörter (ETH Zurich, KOF Swiss Economic Institute, 2016)
This paper investigates the causal relationship between firms' research and development expenditures (R&D) and their investments into fixed capital. The literature provides two contrasting views in this respect. The first view holds that a firm's research activity causes, via the creation of inventions, subsequent investment into fixed capital, as the firm needs additional capacities to produce the new goods or services that follow from the inventions. The second view holds that firms' fixed capital investments cause intensified research activity, as novel capital goods from external suppliers offer the firms' researchers a wide range of additional technical possibilities of how to build new prototypes. Using panel data of Swiss firms ranging from 1990 to 2014, the paper applies, contrasting the existing empirical literature only based on VARs, a 2SLS approach to uncover the direction of causality between R&D and fixed capital investment. In order to obtain exogenous instruments, the paper exploits shocks to i) technological opportunities and ii) sales from capital goods suppliers. Results show a one-way causal relationship; we find evidence for that firms' R&D expenditures cause fixed capital investments, but we do not find evidence for the reverse effect. When additionally looking at innovation performance, R&D activities turn out to be complementary to fixed capital investment, in the sense that they markedly increase the expected return on investment. Thus, increasing research activity may not just be valuable for long-run economic growth but, via investment, may also give the economy a head start in times of a prolonged economic downturn.
Keywords: O33; 330; Investment; Research and Development; Invention; Technological Opportunities; Complementarity